What are the most common legal bases for personal data processing in the context of local public authorities’ activities? Legal obligation vs Public Interest - Kozhuharova, Denitsa; Kutsarova, Dilyana (Wydawnictwo C.H. Beck, 2019)
The current paper offers an overview on several provisions enshrined in Article 6 of the General Data Protection Regulation from the perspective of local public authorities. It advocates that administrative law notions might facilitate municipalities to make a better distinction when they process personal information either on the basis of legal obligation or for the performance of a task carried out in the public interest, or for the exercise of official authority vested in the controller. The paper reviews data subject rights implications in this relation. It also touches upon legitimate interests and consents applicability in day-to-day operations of personal data processing executed by local public authorities.
Keywords: data protection; privacy; GDPR; legal bases; public interest; legal obligation